2021
DOI: 10.3390/ijms22115550
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Action of Mulberry miR156 in the Vegetative Phase Transition

Abstract: The vegetative phase transition is a prerequisite for flowering in angiosperm plants. Mulberry miR156 has been confirmed to be a crucial factor in the vegetative phase transition in Arabidopsis thaliana. The over-expression of miR156 in transgenic Populus × canadensis dramatically prolongs the juvenile phase. Here, we find that the expression of mno-miR156 decreases with age in all tissues in mulberry, which led us to study the hierarchical action of miR156 in mulberry. Utilizing degradome sequencing and dual-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…In mulberry, the TT2L1 and TT2L2 proteins interact with bHLH3 or GL3 to promote proanthocyanidin (the multimer of catechin or epicatechin) accumulation [40]. Furthermore, mulberry genome sequencing has been completed [33,41], and our previous study also verified that nine mulberry SPL genes are directly regulated by miR156 [42]. However, to date, systematic research on mulberry SPL genes is still lacking; consequently, the specific molecular biological functions of SBP-box transcription factor genes in development and stress responses remain unclear.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In mulberry, the TT2L1 and TT2L2 proteins interact with bHLH3 or GL3 to promote proanthocyanidin (the multimer of catechin or epicatechin) accumulation [40]. Furthermore, mulberry genome sequencing has been completed [33,41], and our previous study also verified that nine mulberry SPL genes are directly regulated by miR156 [42]. However, to date, systematic research on mulberry SPL genes is still lacking; consequently, the specific molecular biological functions of SBP-box transcription factor genes in development and stress responses remain unclear.…”
Section: Introductionmentioning
confidence: 54%
“…These results suggest that plant SPL genes may have originated from common ancestral genes, but some SPL genes may have been differentiated separately between monocots and eudicots. Nine MnSPL genes have been verified as the target genes of miR156 in mulberry [42]. Here, we found that most of the miR156-target MnSPLs clustered with miR156-target AtSPLs, except for MnSPL7 and MnSPL14 (Figure 2).…”
Section: Identification and Analysis Of The Spl Gene Family In Mulberrymentioning
confidence: 68%
“…For example, miR398 and its target partner superoxide dismutase1 (CSD1) are involved in the regulation of abscisic acid (ABA) and salt stress related pathways of poplar and Arabidopsis thaliana [53]; PtmiR169o can enhance the drought resistance of poplar by inhibiting the expression of its target gene PtNF-YA6, thereby promoting its growth [39]. In addition, we also found that a large number of circRNAs target miRNA family members that play a key role in plant organ development, growth phase transition, and phenological regulation, such as the miR156 and miR157 families [38,40,[54][55][56]. miRNA156/157 combines with the miRNA recognition element (MRE) of the SPL3 gene of Arabidopsis thaliana to promote early flowering [38].…”
Section: Functional Prediction Of Circrnas Related To the Formation O...mentioning
confidence: 83%
“…Among the different types of miRNA, more members of the miR156, miR157, and miR169 families were targeted (Table S17). Some members of these families have been confirmed to affect the plant stress response, organ development, growth phase transformation, and phenological regulation by regulating the expression of their target genes [38][39][40]. miR5021, miR156, miR5641, miR5649, and miR5998 were all targeted by a large number of circRNAs (Table S17).…”
Section: Circrnas Regulate the Formation Of Different Growth Potentia...mentioning
confidence: 99%
See 1 more Smart Citation